No fats, no fems, no problems? Working out and the gay muscled body. (December 2022) - Chow, Jeremy
This article investigates two ubiquitous slogans that circulate among gay social media apps: 'No Fats, No Fems' and 'Masc for Masc'. In their recurrence, both offer gendered readings of corporeality and ability, which equate muscled bodies with forms of desirable masculinity. In collecting data from SCRUFF, I document how gay male social media apps generate narrow definitions of masculinity that, like the slogans, uphold physical fitness and compulsory able-bodiedness as hallmarks of gay desirability. Alongside these trends, I highlight 'working out' as an exceptional form of gay male labour that prioritises ability and transforms the muscled body into a commodity that is successfully advertised on these apps.